Analysis in Assessing Environmental, Social, and Governance (ESG) Risks and Impact on Business Sustainability - Natasya, Anisha; Soeratin, Harry Z. (Jurnal Ecoment Global, 2024)
Objective: This study aims to explore auditors' analysis in assessing risks related to Environmental, Social, and Governance (ESG) and their impact on business sustainability. Design/Method/Approach: The research method used is descriptive analysis using the literature review method. Literature reviews can explain the background of a topic's research, the reasons why a topic is important to research, and find relationships between studies or research ideas. Findings:Environmental, Social, and Governanceaudits have a significant positive impact on business sustainability. Increased transparency, strengthened governance, and more effective risk management make companies better prepared to face sustainability challenges. Originality/Value:NoveltyThis study discusses the analysis in assessing Environmental, Social and Governance Risks and their impact on Business Sustainability. Practical/policy implications:This research is expected to help management in ensuring the long-term sustainability of the company, and help auditors in analyzing Environmental, Social, and Governance (ESG) risks. Keywords:Auditors, Environmental, Social, and Governance (ESG), literature review